Automated document preprocessing for text categorization - Abd Rahman, Suraya (2006)
This study deals with the document preprocessing step of Text Categorization System (TCS) done by previous researcher. Previously, the document used for TCS was entered manually by key-in the abstract of the document into database.So it will burden if it involves a large volume of articles.In this study, the extraction based approach was applied in order to automate the document preprocessing. One module was added into the prototype of text categorization system that is used to add document into database.